Converging on Ancient Bones: A Review of the Evidence for the Close Relatedness of Humans (Homo sapiens) and Spotted Hyenas (Crocuta crocuta) - Baynes-Rock, Marcus (Humanimalia, 2015)
The majority of spotted hyena studies are conducted in places such as national parks and reserves where there are few humans present other than the researchers. I argue that this reflects a perception that “real” hyenas are those largely unaffected by contact with humans. This is at odds with fossil evidence which demonstrates a long, shared history of human/hyena co-evolution since our ancestors first came together on the African continent more than six million years ago. From that time human ancestors adopted lifeways that brought them into direct competition with hyena ancestors over carcass-based resources. These relations of competition and coexistence persisted through dispersals across Eurasia and into the late Pleistocene. So too in Africa, our respective ancestors competed over prey for millions of years. There hyena/human competition over livestock animals is a vestige of ancient enmity that marks both species as enemies. In light of this evidence I present a reconfiguration of what it is to be hyena or human. Using a theoretical framework developed by Jacob von Uexküll I argue that hyenas are to a great degree human-like and vice versa. This conclusion in turn undermines human exceptionalism by undermining the “non-animalness” which is normally held to separate humans from other species.